columbella: an evil woman's plot threatens a young girl escaping from her own nightmare past - Whitney, Phyllis; Phyllis Whitney (Great Britain Coronet Books, 1966)
How could jessica combat the evil charm of beautiful columbella? the woman who called herself columbella seemed to possess the very essence of femininity. She had breathtaking beauty, a taste for youth and was jealous of her own daughter. On the exotic island of St Thomas it seemed that columbella had everything she wanted. For years she had drawn an all but invisible net around the husband she mocked and the young daughter she dazzled. Now, on the night of the shell in the silver caribbean moonlight, columbella's destructive net was tightening. Only her daughter's governess, open-hearted and inexperience, stood in columbella's way, fighting reclessly for her own happiness and for the saftey of another woman's child. Only jessica, feeling from her own troubled past, could unlock the secret of columbella's mysterious shells in time to save the man she loved from complete destruction.
English